2004
DOI: 10.1088/0953-8984/16/23/022
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Sr substitution on superconductivity in Hg2(BaySry)2YCu2O8  : I. A neutron powder diffraction study

Abstract: The effect of Sr chemical pressure on superconductivity was investigated in Hg 2 (Ba 1−y Sr y ) 2 YCu 2 O 8−δ . The samples were synthesized at high pressure and high temperature from y = 0.0 to full substitution, y = 1.0. These Sr substituted compounds are superconducting, without Ca doping on the Y site, and show a T c increasing with Sr, reaching 42 K for y = 1.0. A detailed neutron powder diffraction study compares the structural changes induced by this chemical Sr/Ba substitution and the mechanical pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…In the previous paper [1], we showed that Sr induces an overall shrinkage of the structure due to its ionic radius being smaller than that of Ba. The detailed analysis of the position shifts of each atom is summarized as follows.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In the previous paper [1], we showed that Sr induces an overall shrinkage of the structure due to its ionic radius being smaller than that of Ba. The detailed analysis of the position shifts of each atom is summarized as follows.…”
Section: Introductionmentioning
confidence: 88%
“…It is also often associated with a chemical pressure effect accounting for the smaller size of Sr substituted for Ba. In part I, we extracted precise structural data on bond lengths by neutron powder diffraction (NPD) analysis [1]. We studied the effect of Sr substitution on the barium site in the Hg 2 (Ba 1−y Sr y ) 2 YCu 2 O 8−δ series and compared to the effect of mechanical pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Toulemonde et al pada tahun 2004 telah meneliti bagaimana pengaruh tekanan kimia Sr pada superkonduktivitas pada Hg 2 (Ba 1-y Sr y ) 2 YCu 2 O 8- [9]. Dari penelitian tersebut diperoleh bahwa sampel tersubstitusi Sr menunjukkan Tc yang meningkat dengan substitusi Sr yaitu mencapai 42 K untuk y = 1,0.…”
Section: Landasan Teoriunclassified
“…A variety of examples of such chemical-pressure utility are found among, e.g., high-T c superconductive (HTS) copper oxides and colossal magnetoresistance (CMR) manganese oxides. [1][2][3] Chemical pressure is generated through "isovalent smaller-for-larger" cation substitution, typically involving either divalent alkaline earth or trivalent rare earth elements. To detect pure pressure effects, the substitution should proceed such that the overall cation charge is kept constant.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, the two pressures often act to opposite directions in complex multilayered systems. [1][2][3]6 Despite the widespread utilization of the pressure effects, real understanding behind the apparent outcomes of them is lacking yet.…”
Section: Introductionmentioning
confidence: 99%